The Role of Spirituality in Depression : A Case report - Anabela Amoret Amsori; Roosyidah; Syahrul Gusnaldi Prawidya; Novanthy Nur Rohmadhani Subagyo; Muhammad Azhari Baihaqi; Embun Kumalaratih; Hafid Algristian (Psychosocia : Journal of Applied Psychology and Social Psychology, 2026)
Depression is a psychological condition characterized by persistent sadness, hopelessness, and loss of interest that affects emotional, cognitive, and behavioral functioning. Spirituality is believed to play a significant role in reducing depressive symptoms by fostering inner harmony, emotional resilience, and a sense of meaning in life. This case report explores the relationship between spirituality and depression in a 44-year-old woman diagnosed with major depressive disorder with psychotic features. The patient continues to experience negative emotions such as pessimism, lack of self-confidence, continuous crying, and feelings of inferiority that began after being dismissed from her job, a traumatic event that deeply affected her psychological state. She also experienced a decline in spiritual beliefs and practices, which was attributed to her father’s overly strict and inconsistent religious upbringing. This case highlights the close relationship between spirituality and mental health, demonstrating that spiritual well-being can serve as a protective factor against depression by enhancing emotional stability, personal resilience, and positive psychological adjustment. The integration of spiritual care into mental health interventions is therefore essential, as it may improve recovery outcomes and enhance the overall quality of life for individuals experiencing depression.